(untitled) ("Journal "U". Economy. Management. Finance.", 2025)
The article considers the possibility of using an HR brand as a tool for attracting candidates to Russian airport operator companies. To achieve this goal, a survey was conducted, which included a sample of 100 people (candidates for work in the company and newly hired employees). The results of the study demonstrated the degree of awareness about the employer’s brand, the image of the company (from the candidates’ point of view), the quality of the implementation of the main components of the HR brand, and the influence of the employer’s brand on the decision to choose a job. Recommendations have also been developed to improve work with this technology, which can be used by HR managers and heads of organizations to apply the HR brand as a tool for attracting candidates.